THE INFLUENCE OF SELF EFFICACY AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE PNS IN TEMANGGUNG - Ermayasari, Inas Zaviroh Putri (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The study aimed to determine the influence of self efficacy and employee engagement on the employee performance civil cervants in Temanggung. This research used a quantitative descriptive methods. The method used in probability sampling with 100 respondents. Primary data collected by questionnaire and had been tested for validity and reliability. This research was processed using data analysis of the SPSS version 24 program. The results of the research show that self efficacy and employee engagement affect employee performance of civil servants in Temanggung.